Analysis and testing of the IPB pico-hydro emulation platform with grid connection - Ribeiro, Gabriela Moreira (2021)
The global context in which there is a need to reduce environmental impacts intensifies the search for new technologies for renewable sources. In addition to environmental issues, access to basic rights and social inclusion are also motivation for electricity generation, in a context including distributed generation (DG). Currently, the pico hydro power plant is an attractive application because of its resource availability; also, it is an interesting solution for a microgrid (on-grid or off-grid). On the other hand, usually, the conversion system is not "plug and play". This project presents the tests of convertion system for a "plug and play" solution, using different turbines and water wheel, permanent magnet synchronous generators (PMSG) and photovoltaic (PV) inverters. In this approach, generators can work at variable speed, having an overvoltage protection circuit. The prerequisites for device integration must be considered: power compatibility, minimum and maximum limit voltage, and the maximum current of PV inverter. The tests were done in the pico-hydro emulation platform, in the Superior School of Technology and Management (ESTiG). The low head propeller, Turgo, and Pelton turbines are tested in the emulation platform; as well as the vertical axis water wheel. The turbines were connected to the grid using SOLAX inverters (up to 1650 W) and OMNIK (up to 2300 W), presenting satisfactory results in both. The water wheel tests used five microinverters (up to 300 W), showing grid connection with three: BEON, GWL, and INVOLAR.